Environmental and occupational impacts from U.S. beef slaughtering are of same magnitude of beef foodborne illnesses on human health. (August 2019) - Li, Shaobin; Subbiah, Jeyamkondan; Dvorak, Bruce
Abstract: Foodborne pathogens and occupational hazards are two primary safety concerns for U.S. beef slaughterhouses. The anthropogenic environmental impacts due to intensive resource use and pollution also exert threats to human health. Quantifying human health impacts from various sources remain a grand sustainability challenge for U.S. beef industry. We develop a framework to systematically estimate and compare human health impacts associated with U.S. beef foodborne illnesses from major pathogens and environmental impacts and occupational hazards from U.S. beef slaughtering on a common metric, disability-adjusted life year (DALY). Foodborne illnesses and occupational hazards are estimated by synthesizing published data and methodologies while environmental impacts are quantified using life cycle assessment. In spite of inherent uncertainties in estimation, results show that the environmental impacts and occupational hazards from beef slaughtering are of same magnitude with foodborne illnesses from beef consumption on human health. Salmonella and Clostridium perfringens contribute 51% and 28%, respectively, to the beef foodborne DALY; Global warming and fine particulate matter formation, due to electricity and natural gas use, are primary drivers for environmental DALY, accounting 62% and 28%, respectively. Occupational DALY is on average lower than environmental DALY from beef slaughtering and foodborne DALY. The impact of new food safety interventions that use additional resources to improve food safety should be considered jointly with environmental impacts and occupational hazards to avoid unintended shifts and net increase of human health impacts. The methodology and results from this study provide a new perspective on reforms of the U.S. food safety regulations building toward sustainability in the food processing industry. Highlights: Electricity and natural gas contribute 80% of environmental DALY during beef processing. 42% of environmental DALY is from processes directly related to microbial food safety. Salmonella and Clostridium perfringens causes 79% of beef foodborne illness DALY. Environmental and occupational DALY are of same magnitude of beef foodborne DALY. The developed framework has broader implications of human health caused by other meat industry.